Analyzing the Impact of Verb Extensions on Semantic Role Variability in Kiha - Makulilo, Prisca Boniphace (Journal of Language and Literature, 2024)
The research analyzes the impact of verb extensions on semantic role variability in Kiha. In doing so, the study explores how verb extensions affect the semantic roles of arguments in a sentence, spotting trends and patterns in the usage of verb extensions, and the differences in their corresponding semantic roles. Verb extensions on semantic role variability are linguistic aspects that scholars did not find particularly fascinating to research. This study is interested in examining how verb extensions affect semantic role variability. Due to their proficiency in both writing and speaking Kiha, two informants who are native speakers, aged 83 and 73, were selected for the data collection process using the qualitative approach and elicitation technique. Data is presented using the fragmentation method, and coding is applied to ensure that the study is consistent with other studies that were cited in the literature. Lexical Mapping Theory is the framework for examining the data. The study concludes that the applicative verb extension has four semantic roles: beneficiary, recipient, reason/cause, and locative. Likewise, causative verb extension has two semantic roles: causee and instrument. Reciprocal and passive verb extensions have shared participant semantic roles.